Dr. Susan I. Moody's travels to Iran, 1909-1934: courageous odyssey - Mahmoudi, Hoda (Routledge research in gender and history, 2024)
A woman of her time -- A woman of faith -- Educator, artist, physician -- A new believer -- A new faith -- In the presence of 'Abdu'l-Bahá -- The road to Persia -- At home in Tehran -- A school for girls -- Murder in Tehran -- Strong of heart -- A final season.